Numerična analiza zaporednega tlačnega polnjenja pri hitrotekočih dizelskih motorjih - Medica, Vladimir (Strojniški vestnik, 1999)
Turbocharged diesel engines for road-going and off-road vehicles operate over a wide range of engine speeds and loads. It is very difficult to cover effectively the whole operational range using only one turbocharger, so many new strategies in the supercharging of such engines are available. In this paper, a Diesel engine using a sequential turbocharging systems, comprising two turbochargers is analyzed. Results are compared with the same engine usinga single turbocharger, with fixed turbine geometry, matched to the engine's operational range, and to the same engine equipped with a turbocharger with variable turbine geometry. Steady state and transient operational characteristics are compared. The results show some advantages of the sequential turbocharging system in steady state and transient engine operation.
Keywords: motorji dieselski; polnjenje tlačno; modeliranje numerično; karakteristike; dizelski motorji; numerična analiza; polnjenje